Impact of The Supreme Court’s Case -Law on the Realisation of Procedural and Substantive Rights in Civil Procedure; Specific Aspects in Latvian Civil Procedure (Global Journal of Management and Business Research, 2023)
The author s article is devoted to procedural justice in civil proceedings and factors affecting it The author conducts research in her home country i e the Republic of Latvia on the practical consequences of the norms governing civil proceedings in connection with the application of case law which the author associates with a factor affecting procedural justice It should be explained here that the Republic of Latvia belongs to the continental European law group therefore the term case law means the highest court instances i e Judgments of the Senate of the Supreme Court of the Republic of Latvia which contain explanations about the correct application of the procedural and or material norm or the interpretation of this norm
Keywords: justice; supreme court’s case law; civil procedure; procedural rights